Dynamic Access Control for Multi-Privileged Group Communications - MA, Di (Institutional Knowledge at Singapore Management University, 2004)
Recently, there is an increase in the number of group communication applications which support multiple service groups of different access privileges. Traditional access control schemes for group applications assume that all the group members have the same access privilege and mostly focus on how to reduce rekeying messages upon user joining and leaving. Relatively little research effort has been spent to address security issues for group communications supporting multiple access privileges. In this paper, we propose a dynamic access control scheme for group communications which support multiple service groups with different access privileges. Our scheme allows dynamic formation of service groups and maintains forward/backward security when users switch service groups.